Role of Heme-Oxygenase- 1 in Attenuated Cardioprotective Effect of Ischemic Preconditioning in Hyperlipidemic Myocardium (Global Journal of Medical Research, 2017)
Nitric Oxide (NO) is responsible for cardioprotective effect of ischemic preconditioning (IPC). Heme Oxygenase-1 (HO-1) facilitates release of NO by disrupting caveolin-eNOS complex. Both, the expression/activity of HO-1 and the IPC mediated cardioprotection are decreased significantly in hyperlipidemia. In this study the role of HO-1 in attenuation of IPC-induced cardioprotective effect in hyperlipidemic rat was investigated. Hyperlipidemia was induced by feeding high fat diet to Wistar rats. Isolated Langendorff heart preparation model was used. Cardioprotective effect was assessed by myocardial infarct size measurement and release of Lactate Dehydrogenase (LDH), Creatine Kinase (CK-MB) in coronary effluent. Nitrite estimation was done to indirectly infer the level of cardiac NO production. In hyperlipidemic rat, IPC-induced cardioprotection and release of NO were significantly decreased. Perfusion with sodium nitrite (NO precursor) and pre-treatment with daidzein (DDZ) (caveolin inhibitor) and hemin (HO-1 inducer), alone or in combination significantly restored the attenuated cardioprotective effect of IPC in hyperlipidemic rats. Administration of zinc protoporphyrin (ZnPP), HO-1 inhibitor, significantly abolished the observed cardioprotection in hemin pre-treated hyperlipidemic rat. The significant restoration of the attenuated cardioprotective effect of IPC following induction of HO-1 by hemin in hyperlipidemia was observed. The results indicated that attenuation of IPC-induced cardioprotective effect may be due to the decrease in HO-1 induced NO release in hyperlipidemic rat heart.
Keywords: heme oxygenase-1; ischemic preconditioning; hyperlipidemic rat heart; hemin; diadzein